2009
DOI: 10.1093/eurpub/ckp085
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of qualitative research to the development of tailor-made community-based interventions in primary care: a review

Abstract: Pragmatic trials seem to be oxymoronic. Although the pragmatic trial methodology establishes the effectiveness of interventions under natural, non-experimental conditions, no pragmatic fit is allowed. Qualitative research's contribution to the development of tailor-made community-based interventions lies in providing ongoing evaluations of the dilemmas faced in pragmatic trials and allowing for the development of true tailor-made interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 24 publications
1
60
0
Order By: Relevance
“…A common approach to describing the use of qualitative research with RCTs is a temporal framework, which considers how qualitative research can be used before, during, or after a trial (Creswell et al, 2009;Jansen et al, 2009;Lewin et al, 2009;Sandelowski, 1996). It is worth relecting on what these authors mean by trial before exploring how qualitative research is used before during and after the trial.…”
Section: He Temporal Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…A common approach to describing the use of qualitative research with RCTs is a temporal framework, which considers how qualitative research can be used before, during, or after a trial (Creswell et al, 2009;Jansen et al, 2009;Lewin et al, 2009;Sandelowski, 1996). It is worth relecting on what these authors mean by trial before exploring how qualitative research is used before during and after the trial.…”
Section: He Temporal Frameworkmentioning
confidence: 99%
“…In Table 23.1 we display the diferent work authors have suggested qualitative research can do before, during, and after the trial, and then we go on to explore these stages in more detail. Before the trial To "trial" the trial Sandelowski, 1996 To develop an instrument when a suitable instrument is not available to measure an outcome in a trial or select appropriate outcome measures Creswell et al, 2009;Lewin et al, 2009 To develop recruitment or consent practices, estimate recruitment or retention, and understand the burden placed on trial participants and caregivers MRC, 2000MRC, , 2008Creswell et al, 2009 To understand the context in which the trial or intervention occurs to ensure that the intervention will work in a particular context or to identify any issues that may occur Creswell et al, 2009;Jansen et al, 2009;Lewin et al, 2009 To support the need for an intervention by identifying the evidence base and identifying or developing theory and hypotheses MRC, 2000MRC, , 2008Creswell et al, 2009;Jansen et al, 2009;Lewin et al, 2009 (continued) OUP UNCORRECTED PROOF -FIRSTPROOFS, Wed Mar 04 2015, NEWGEN…”
Section: He Temporal Frameworkmentioning
confidence: 99%
See 3 more Smart Citations